ACTIVATED SIMPLE SUPERPHOSPHATE BASED ON NODULAR PHOSPHORITE MEAL OF KARAKAPAKSTAN (Scientific journal of the Fergana State University, 2023)
The physico-chemical and mineral composition of Karakalpak phosphorites has been studied. Phosphate mineral mainly consists of kurskite, francolite and various additives (calcite, magnesite, glauconite, quartz, feldspar, etc.) in equal amounts. The goal is to obtain simple superphosphates by activating Karakalpak phosphorites at various concentrations and norms of sulfuric acid, as well as to study their physicochemical and commercial properties. The obtained products were investigated by the methods of physicochemical analysis. In particular, the amount of P2O5 was determined by photocolorimetric titration, the amount of CaO - by complexometric titration. For acid activation of phosphate rock, decomposition was carried out at sulfuric acid concentrations of 68, 80 and 93% and acidity rate of 60-100% at a temperature of 70 ℃. The optimal rate of sulfuric acid for processing phosphate is considered to be 75% of the stoichiometry. The relative amount of the water-soluble form of Р2О5 in the products exceeds 60%. In products obtained from Karakalpak phosphorites, a high content of assimilable and water-soluble P2O5 was found. The results of the research indicate the possibility of obtaining simple superphosphate from the Khodzhakul nodular phosphate flour of acceptable quality.